Busy. Please wait.

show password
Forgot Password?

Don't have an account?  Sign up 

Username is available taken
show password


Make sure to remember your password. If you forget it there is no way for StudyStack to send you a reset link. You would need to create a new account.

By signing up, I agree to StudyStack's Terms of Service and Privacy Policy.

Already a StudyStack user? Log In

Reset Password
Enter the associated with your account, and we'll email you a link to reset your password.

Remove ads
Don't know
remaining cards
To flip the current card, click it or press the Spacebar key.  To move the current card to one of the three colored boxes, click on the box.  You may also press the UP ARROW key to move the card to the "Know" box, the DOWN ARROW key to move the card to the "Don't know" box, or the RIGHT ARROW key to move the card to the Remaining box.  You may also click on the card displayed in any of the three boxes to bring that card back to the center.

Pass complete!

"Know" box contains:
Time elapsed:
restart all cards

Embed Code - If you would like this activity on your web page, copy the script below and paste it into your web page.

  Normal Size     Small Size show me how

Simultaneous Eqns

Methods and steps for solving algebraic simultaneous equations

Simultaneous Equations Addition/Subtraction/Elimination Method 1. Multiply one or both equations by some number to make the number in front of one of the variables the same in each equation
Elimination Method Example 3x + 3y = 24 2x + y = 13 MULTIPLY bottom equation by -3
Elimination Method Example(Card 2) Equations become: 3x + 3x = 24 -6x - 3y = -39
Elimination Method Example (Card 3) 2. ADD the equations to eliminate the y variable. You get: -3x = -15. SOLVE for x to get x = 5.
Elimination Method Example (Card 4) To solve for y, plug the value x = 5 back into either original equation. EXAMPLE: 2(5) + y = 13 10 + y = 13 y = 13 - 10, so y = 3.
Simultaneous Equations Substitution Method For this method, you need to isolate one of the variables on one side of the equation
Substitution Method Example (Card 1) Let's use the equations x + y = 3 2x + 3y = 8
Substitution Method (Card 2) In the first equation, move everything but the x to the right side of the equation to get: x = 3 - y
Substitution Method (Card 3) Now wherever there is an x in the second equation, we can substitute 3 - y. So the equation 2x + 3y = 8 becomes 2(3 - y) + 3y = 8.
Substitution Method (Card 4) When we simplify this, we get 6 - 2y + 3y = 8. This becomes 6 + y = 8 or y = 8 - 6 = 2
Substitution Method (Card 5) Now, to solve for x, simply plug the value for y, which is 2, back into the first equation: x + 2 = 3. So, x = 1.
Created by: wronawoman